THE CHANGE OF THE CONTENT AND FORM OF THE GHAZAL IN TAJIK LITERATURE (Scientific journal of the Fergana State University, 2023)
The poetic form of the ghazal is one of the most popular lyrical forms of Tajik literature, which has always been in the forefront. Tajik literature does not remember a poet who completely abandoned ghazal poetry. That is, the ghazal remained the most popular form of poetry at all times. However, its content underwent partial changes depending on the times.This poetic form, which was originally aimed at singing romantic moments, expressing mystical feelings and expressing philosophical opinions, began to embody political, social and historical moments in one or two verses. Gradually, ghazals were created, the number of verses with political and social themes increased. And starting from the end of the 19th century and the beginning of the 20th century, the theme of the ghazal has completely changed.At the time of independence, the gazelle traveled a new path of development. Poets such as Abdullah Subhan, Paymon, Jafari Muhammad and others had considerable researches in this context, whose recognition and evaluation will help to determine the place of this genre in the Tajik-language literature of Uzbekistan.